The Effect of Collaborative Problem Solving Learning Model on Students' Collaboration Skills in Chemistry Learning - Lestari, Wahyu Yunita; Erika, Farah; Rahmadani, Agung (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The low collaboration skills of students are due to the less-than-optimal role of the teacher in fostering interpersonal skills and cooperation in the classroom. Selecting an appropriate learning model is key to effectively enhancing students' collaboration skills. Therefore, the Collaborative Problem Solving (CPS) learning model optimizes students' collaboration skills. This study aims to determine the effect of the Collaborative Problem Solving (CPS) model on students' collaboration skills in elements, compounds, and mixtures. The approach employed is a quasi-experimental design utilizing a non-equivalent control group format. All 8th-grade junior high school students in Samarinda for the 2023/2024 academic year served as the population in this study. Class VIII A was assigned as the experimental group, whereas Class VIII B was the control group. The sample was selected using purposive sampling based on the subject teacher’s considerations, including classroom participation, group collaboration, and peer interaction. The instrument used was a collaboration skills questionnaire consisting of 25 statement items, utilizing a 5-point Likert scale. Data collection was also carried out using an observation sheet developed based on the indicators of collaboration skills. The data were analyzed descriptively after being collected through observations and collaboration skill questionnaires. The findings indicated that the experimental group achieved a higher average score than the control group, indicating that the CPS model syntax positively improved students' collaboration skills.